Lymphotropic herpes virus (EBV, HHV-6, HHV-8) DNA sequences in HIV negative Castleman's disease. Issue 4 (August 1996) - Barozzi, P; Luppi, M; Masini, L; Marasca, R; Savarino, M; Morselli, M; Ferrari, M G; Bevini, M; Bonacorsi, G; Torelli, G
Abstract : Aim —To evaluate the possible involvement of lymphotropic herpes viruses in Castleman's disease. Methods —Archival formalin fixed, paraffin wax embedded biopsy specimens from 16 HIV negative patients (11 with localised and five of multicentric disease) were studied. Epstein-Barr virus (EBV), human herpes virus-6 (HHV-6) and human herpes virus-8 (HHV-8) DNA was detected using PCR. PCR was also used to characterise the EBV genomes and the clonal status of the lesions. Results —EBV sequences were identified in nine (56%) cases. The main EBV genotype detected was type 1. Two (12%) cases were positive for both HHV-6 and EBV sequences. HHV-8 sequences were detected in one case of localised Castleman's disease, the sequence of which differed from that of the HHV-8 prototype. No clonal immunoglobulin gene rearrangements were found. Conclusions —EBV DNA was detected in a substantial proportion of cases, suggesting that it may have a role in the pathogenesis of Castleman's disease, unlike HHV-6 which was detected rarely. This is the first report of HHV-8 specific sequences in the localised from of the disease.